Mechanistic Insight into Salt Tolerance of Acacia auriculiformis: The Importance of Ion Selectivity, Osmoprotection, Tissue Tolerance, and Na+ Exclusion - Rahman, Md. M.; Rahman, Md. A.; Miah, Md. G.; Saha, Satya R.; Karim, M. A.; Mostofa, Mohammad G. (Frontiers in Plant Science, 2017)
Salinity, one of the major environmental constraints, threatens soil health and consequently agricultural productivity worldwide. Acacia auriculiformis, being a halophyte, offers diverse benefits against soil salinity, however; the defense mechanisms underlying salt-tolerant capacity in A. auriculiformis are still elusive. In this study, we aimed to elucidate mechanisms regulating the adaptability of the multi-purpose perennial species A. auriculiformis to salt stress. The growth, ion homeostasis, osmoprotection, tissue tolerance and Na+ exclusion, and anatomical adjustments of A. auriculiformis grown in varied doses of seawater for 90 d and 150 d were assessed. Results showed that diluted seawater caused notable reductions in the level of growth-related parameters, relative water content, stomatal conductance, photosynthetic pigments, proteins, and carbohydrates in dose- and time-dependent manners. However, the percent reduction of these parameters did not exceed 50% of those of control plants. Na+ content in phyllodes and roots increased with increasing levels of salinity, whereas K+ content and K+/Na+ ratio decreased significantly in comparison with control plants. A. auriculiformis retained more Na+ in the roots and maintained higher levels of K+, Ca2+ and Mg2+, and K+/Na+ ratio in phyllodes than roots through ion selective capacity. The contents of proline, total free amino acids, total sugars and reducing sugars significantly accumulated together with the levels of malondialdehyde and electrolyte leakage in the phyllodes, particularly at day 150th of salt treatment. Anatomical investigations of the cross-sections of phyllodes, stems and roots revealed that the thickness of palisade parenchyma, upper and lower epidermes, and compactness of epidermes, exodermises, cortex and pith decreased in a salt concentration-dependent manner relative to control counterparts. Although vascular bundle and epidermes of the stems were disrupted, increased thickness of endodermis and cellular area indicated a higher efficiency of sequestrating Na+ in plant tissues. Furthermore, the estimated values for Na+ exclusion and tissue tolerance index suggested that A. auriculiformis efficiently adopted these two mechanisms to address higher salinity levels. Our results conclude that the salinity tolerance of A. auriculiformis is closely associated with ion selectivity, increased accumulation of osmoprotectants, efficient Na+ retention in roots, anatomical adjustments, Na+ exclusion and tissue tolerance mechanisms.